Comparative effects of different loads of aerobic exercise on lipid metabolism in MASLD rats: a perspective from the gut-liver axis - Dongkun, Deng; Qingfeng, Jiang; Chang, Li; Yunhua, Lin; Jiaming, Shi; Yufei, Liu; Lin, Xu (Frontiers in Medicine, 2025)
ObjectiveExercise training has been shown to be effective in ameliorating obesity-related diseases, but the therapeutic effects of different loads of exercise on metabolic dysfunction-associated steatotic liver disease (MASLD) as well as the underlying mechanisms by which exercise is based on the enterohepatic axis and thus alleviates MASLD are still unclear. Therefore, the present study aimed to clarify the optimal exercise load for improving MASLD and to reveal its molecular mechanisms in the treatment of metabolic-associated fatty liver disease (MASLD) in the context of the enterohepatic axis.MethodsForty male rats were randomly divided into two groups: NFD (n = 8) and HFD (n = 32). The rats in the NFD group were fed a normal chow, while those in the HFD group were fed a high-fat chow. Following an eight-week period of observation, the rats in the high-fat diet (HFD) group were separated into four further groups for the purpose of analysis: (1) LEH (low-load aerobic exercise)-8; (2) MEH (medium-load aerobic exercise)-8; (3) HEH (high-load aerobic exercise)-8; and (4) HFD-8. At the conclusion of the experiment, blood, liver, and ileum samples were collected for analysis of the rats’ baseline conditions, hepatic lipid metabolism, bile acid pathway and gut microbiota, and synthesis of analyses.ResultsThe development of lipid metabolism disorders, insulin resistance, and hepatic steatosis in MASLD rats was improved to different degrees in all three exercise modes. It also restored the high-fat diet (HFD)-induced intestinal barrier dysfunction and balanced the homeostasis of the gut-liver axis. Aerobic exercise also upregulated bile acid-related gene expression modulated butyrate-producing bacterial taxa, and adjusted the abundance of butyrate-generating bacteria.ConclusionCompared with low-load aerobic exercise, medium- and high-load aerobic exercise was more beneficial in modulating lipid metabolism dysfunction in MASLD rats, and to some extent, high-load aerobic exercise was superior to medium-load aerobic exercise.